Average molecular weight and molecular weight distribution of the Vietnamese acacia pulps. - Khai, Doan Mai; Nhan, Phan Duc; Hoang, Trinh Dac (Vietnam Journal of Chemistry, 2017)
The average molecular weight (MW) and the molecular weight distribution (MWD) of the several acacia pulps produced from wood of acacia tree in Vietnam were investigated. These chosen pulps had the various brightness were produced by Kraft method and bleaching. The MW was determined by viscosity of the pulps in copper-ammonium complex. The MWD was determined by fractional method which was carried out by dissolving pulp in the various phosphoric acids from 73.3 to 83 % in weight. The results show that these pulps have an average degree of polymerization (DP) in the range from 842 to 878. Additionally, the fraction of pulps with DP lower than 200 units is about 15 percent. The fractionations have the most percentage in the range from 600 to 1050 units. And, there are differences of MW and MWD of pulps from various brightness. Keywords. Acacia pulp, average molecular weight, molecular weight distribution.